Diagnostic and Therapeutic Approach in a Metastatic Vaginal Adenocarcinoma: A Case Report - Egger, Eva Katharina; Ralser, Damian J.; Lindner, Kira; Recker, Florian; Marinova, Milka; Savchenko, Oleksandre; Lau, Jan-Frederic; Mustea, Alexander (Frontiers in Immunology, 2021)
Background Vaginal adenocarcinomas (VAC) are most often reported after intrauterine exposition to diethylstilbestrol (DES). Rarely, VACs are reported as a malignant transformation of vaginal adenosis or endometriosis, in the context of chromosomal abnormalities or malformations of the uterus or the vagina. VACs without DES exposition have a poor prognosis and a significantly worse outcome compared to vaginal squamous cell carcinomas or DES-associated VACs. Objective Here, we report the case of a primarily metastatic VAC, treated successfully with different lines of chemo-, antiangiogenic, antibody, and immunotherapy. Case The 49-year-old patient presented in 5/2018 with a primarily pulmonary metastatic VAC. Significant tumor reduction was seen after six cycles of carboplatin AUC5/paclitaxel 175 mg/m²/bevacizumab 15 mg/kg q3w. Bevacizumab maintenance therapy and later cisplatin mono 50 mg/m² q2w led to local and distant tumor progression. To identify a potential targeted therapy, new tumor biopsies were obtained. Immunohistochemistry revealed ERBB2 expression, and paclitaxel 80 mg/m² weekly plus trastuzumab 4 mg/m² respectively 2 mg/m² q3w was administered. Due to local and pulmonal tumor progression after 6 months and persistent ERBB2 positivity, the therapy was adjusted to trastuzumab emtansine (T-DM1) 3.6 mg/kg q3w; however, the patient remained locally progressive after three cycles of T-DM1 and additionally showed a new bone metastasis. The new tumor biopsies revealed a combined positive score (CPS) of 2 regarding PD-L1, and pembrolizumab 200 mg q3w was initiated. The bone metastasis was radiated and treated with denosumab 120 mg q4w. Extreme tumor regression followed by stable disease was maintained for 9 months. Due to a slow locoregional progress only with new inguinal lymph node and pararectal lymph node metastases, a new tumor biopsy was taken. Molecular profiling showed an ARID1A mutation, a mutational burden of 5.1 mutations per megabase, and no genfusions. Based on these findings, therapy with PD-L1 antibodies, PD-1 antibodies, gemcitabine, or dasatinib was suggested. Therefore, administration of pembrolizumab was continued and local radiation therapy was performed. This led to a decrease in local tumor manifestations and a stable systemic disease. Conclusion Our case demonstrates the diagnostic and therapeutic approach in a patient with primary metastatic vaginal adenocarcinoma. By tumorgenetic profiling, different lines of systemic therapy, namely, antiangiogenic therapy, monoclonal antibody therapy, immunotherapy, and local radiation therapy, were identified and successfully administered.